Revitalizing Justice: Empowering Juvenile Sexual Offenders through a Restorative Approach in Indonesia - Abdurrakhman Alhakim; Teguh Prasetyo; Henry Soelistyo Budi (Universitas Internasional Batam, 2023)
Sexual offense is a serious crime which could pose significant negative impacts on personal level and community. When committed by minors, sexual offense becomes a much more complicated problem and raises many different intricacies. Despite being a popular topic within the legal sphere, restorative justice in Indonesia still has research gap, particularly on the focus of applying restorative justice measures for juvenile sexual offenders. The purpose of this research is to address this research gap and analyze the potentials of using the restorative justice approach to deal with sexual offense cases committed by minors, with the focus of impacts, recovery, and preventing future recidivism. Using the normative legal research method his research dives into the Indonesian legal system to uncover the legal problems that may hinder or discourage people from using this approach, despite the potentials benefits it possesses. Through the statutory approach, this research finds the links within the relevant laws and regulations that may or may not support the use of restorative justice approach to deal with juvenile sexual offenders. The analysis of this finds that the restorative justice approach is indeed beneficial and can help Indonesia in dealing with this issue by not only focusing on delivering justice and recovery the victims, but also holding offenders responsible without sacrificing their youth development and their future.